Characterization of Soils of Narasinghpur Block in Cuttack District of Odisha - Lilan Kumar Behera; Ramawatar Meena; Pragnya Paramita Patel; S.K. Verma; R.N. Meena (Journal of the Indian Society of Soil Science, 2023)
This experiment was carried out to characterize the soils of the study area through the profile study in Cuttack district of Odisha state. In this experiment 15 villages were selected for the profile study. Four samples were collected from each profile from four depths (0-15, 15-30, 30-60 and 60-90 cm). Depth-wise soil samples were processed and analysed for soil texture, bulk density, particle density, porosity, soil pH, electrical conductivity (EC), organic carbon (OC), available nitrogen (N), phosphorus (P), potassium (K), sulphur (S), iron (Fe), zinc (Zn) copper (Cu) and manganese (Mn). Results of soil analysis revealed that soil texture of the studied area was sandy loam and sandy clay loam. Bulk density increased with the increasing depth of the profile and found in the range between 1.23 to 1.45 Mg m-3. The pH values of the soils of the studied area were neutral to slightly alkaline and EC was